2023
DOI: 10.3390/ma16020818
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Long-Time Storage on the Structure and Properties of Multi-Block Thermoplastic Polyurethanes Based on Poly(butylene adipate) Diol and Polycaprolactone Diol

Abstract: A series of semi-crystalline multi-block thermoplastic polyurethanes (TPU), containing poly(butylene adipate) (PBA), polycaprolactone (PCL) and their equimolar mixture (PBA/PCL) as a soft segment was synthesized. The changes in the physical-mechanical and thermal properties of the materials observed in the course of a 36-month storage at room temperature were related to the corresponding structural evolution. The latter was monitored using Fourier transform infrared spectroscopy (FTIR), differential scanning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Consequently, crystallization conditions can be adjusted to control the crystalline phase fraction and the melting temperature. In previous studies, we observed a similar intricate thermal behavior in semicrystalline polyurethane-urea systems during extended storage [21]. The relative content of concurring polyols affects the total degree of crystallinity.…”
Section: Thermal Transitions and Crystallization Kinetics Of Tpussupporting
confidence: 73%
See 1 more Smart Citation
“…Consequently, crystallization conditions can be adjusted to control the crystalline phase fraction and the melting temperature. In previous studies, we observed a similar intricate thermal behavior in semicrystalline polyurethane-urea systems during extended storage [21]. The relative content of concurring polyols affects the total degree of crystallinity.…”
Section: Thermal Transitions and Crystallization Kinetics Of Tpussupporting
confidence: 73%
“…Synthesis of multi-block copolymers was carried out by the three-reactor method developed by us earlier at room temperature (25 • C) [21]. Two crystallizing polydiols were used in different weight ratios PBA/PCL (in wt%) 0/100 for TPU-1(0/100), 50/50 for TPU-2(50/50), 80/20 for TPU-3(80/20), and 100/0 for TPU-4(100/0).…”
Section: Synthesis Of Multi-block Thermoplastic Polyurethane (Tpu)mentioning
confidence: 99%
“…Two polymers, polycarbonate (PC) and thermoplastic polyurethane (TPU), were chosen for this study because of their contrasting mechanical properties. PC has a high modulus and is an amorphous material, whereas TPU is a relatively softer and semi-crystalline material [ 44 , 45 , 46 ]. To ensure consistent printing conditions, the nozzle size, layer width, air gap, raster angle, print orientation, wall count, print speed, and nozzle/bed temperatures were held constant across all the prints.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In our prior research [29,30], we investigated the crystal structure, supramolecular organization, and mechanical properties of TPUs based on PBA and PCL diols, focusing particularly on their evolution during extended storage periods. We emphasized the significance of physical aging and slow crystallization rates in influencing the behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%